AUTOMATED RESOURCE MANAGEMENT SYSTEM FOR THE UTILITY SECTOR BASED ON WIRELESS SENSOR NETWORKS - Igor Nevliudov; Andrii Sliusar; Sofiia Khrustalova; Kirill Khrustalev (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of this study is methods, tools and automated resource management systems for the housing and communal sector. The object of research is the process of controlling resource consumption at housing and communal facilities. The aim of the study is to develop an automated resource management system for the utility sector based on wireless sensor networks. To achieve this goal, the following tasks were solved: a review and analysis of existing methods, tools and automated resource management systems; selection of system components based on technical requirements and taking into account the selected LoRaWAN wireless connection technology; development of a structural diagram and algorithm for the operation of an automated resource management system based on wireless sensor networks; modelling of the process of managing the resources of the utility sector using a wireless sensor network based on t The following methods are used in the work: critical analysis of LoRa technology and other wireless IoT technologies, FOREL and -means clustering methods. The following results were obtained: a general description of the automated resource management system was carried out, its composition and main tasks were determined, and technical requirements for it were established, wireless data transmission technology was selected, on the basis of which the automated resource management system was built, an in-depth comparative analysis of the most effective modern wireless technologies – LoRaWAN and NB-IoT – was carried out, system components were selected, a structural diagram and algorithm for the automated resource management system were developed, and the process of the automated resource management system was modelled. Conclusions: the application of the proposed automated resource management system provides high-quality control of energy consumption at the facilities of the housing and communal sector, makes it possible to control their volume, monitor and analyse energy consumption data, and manage the entire energy supply network as a single system, which is especially necessary in martial law. This approachallows rationalising the consumption of resources by household consumers, which means that the financial costs of energy supply will decrease and the level of energy savings in the country will increase.